DEVELOPMENT ECONOMICS AND THE RUSSIAN REVOLUTION: THE SOVIET INDUSTRIALISATION DEBATE. (24th January 2018) - Azqueta, Diego
Abstract: After the triumph of the October Revolution in Russia the issue of how to develop a backward economy towards a socialist society took pre-eminence. The relationship between agriculture and industry was one of the key issues. In this respect, the Left Opposition argued in favour of a Big Push for industrialisation financed through the exploitation of the peasantry, while the Right Deviation defended adjusting industrial growth to the development of the agricultural surplus. The First 5-Year Plan meant the complete victory of one of these positions. Unfortunately, all discussions were banned subsequently, the leading figures of these two factions were expelled from the Party and many of them executed. Yet, this problem was of the utmost importance for underdeveloped countries, as Development Economics was to discover 25 years later. This new branch of Economics would have benefitted greatly from the lessons of the Soviet experience regarding industrialisation, as well as from the theoretical discussions surrounding it. RESUMEN: Tras el triunfo de la Revolución de Octubre en Rusia el reto de cómo construir el socialismo en una economía atrasada pasó a ocupar el primer plano. Uno de los principales problemas en este sentido era el de las relaciones entre agricultura e industria. La Oposición de Izquierdas abogaba por una industrialización acelerada financiada mediante la explotación del sector agrícola. La Desviación de Derechas argumentaba la necesidad de ajustar el desarrollo industrial al agrícola. El Primer Plan Quinquenal supuso el triunfo absoluto de una de ellas. Desgraciadamente toda discusión fue suprimida después de su aprobación, y los principales protagonistas expulsados del Partido y muchos de ellos ejecutados. Sin embargo, los problemas discutidos eran de la mayor importancia para los países subdesarrollados, como descubriría 25 años después la Economía del Desarrollo. Esta nueva rama de la economía se habría beneficiado enormemente del conocimiento de la experiencia de la industrialización soviética, y de las discusiones teóricas que la acompañaron.